Case Report: Systemic contact dermatitis caused by benzalkonium chloride in a family (a child and parents) - Zhang, Lu; Wang, Yu-Jie; Ma, Yu-Han; Zhao, Guo-Dong; Zhang, Bao-Xiang (Frontiers in Pediatrics, 2025)
BackgroundSystemic contact dermatitis (SCD) occurs due to re-exposure to sensitizing agents via systemic routes, often triggered by drugs, metals, and food additives. Benzalkonium chloride, a cationic surfactant in different household products, can also induce allergic reactions.Case presentationAn 11-year-old girl and her parents presented to our outpatient clinic with erythematous, pruritic plaques and scaling. The girl displayed lesions on her anterior chest and popliteal fossae, moreover her parents had similar lesions on their trunks. Notably, she had no previous allergic responses, and furthermore the laboratory results, including blood counts and IgE levels, were normal. Dermoscopic examination revealed a bright-red background with focal branching vasculature and white scales. Histopathology indicated hyperkeratosis, parakeratosis, and dermal inflammation. However, further investigation uncovered that the family had recently started using a laundry detergent containing benzalkonium chloride. What's more, patch testing with dilutions of the detergent was conducted on the girl and her father, both of whom showed positive reactions, which confirming an allergic response. So they were diagnosed as systemic contact dermatitis (SCD). The rash gradually subsided after the detergent was stopped and the anti-allergy treatment was carried out, and there was no recurrence during the 3-month follow-up.DiscussionAlthough benzalkonium chloride is mainly regarded as an irritant, it can induce an allergic reaction, particularly in pediatric populations. The case indicates that benzalkonium chloride can trigger SCD even with minimal exposure through household products, and further research is needed to elucidate the underlying immunological mechanisms.ConclusionThis case emphasizes that benzalkonium chloride can induce SCD even with minimal exposure through household products. Increased awareness of allergens in everyday consumer goods is essential, and further research is needed to elucidate the underlying immunological mechanisms.